(untitled) (Bioagro, 2022)
It has been shown that the adverse effects of salinity can vary between different varieties of the same plant species. This study was conducted to determine the tolerability of three newly released lines of maize to saline conditions when primed with ethylene diamine tetraacetic acid (EDTA) and salicylic acid (SA) each at 1.0 M concentration; seeds primed with distilled water were used as control. Concentrations of 0, 50, 100, 150 and 300 mM NaCl were tested. The experiment followed a 3x3x5 factorial arrangement of treatments with three replications. The results revealed significant interaction between maize lines and salinity where the germination percentage of line SWAN-LSR-Y was much more affected than the other lines at the salinity level of 50 mM, and its speed of germination was more affected than the others when passing from 150 to 300 mM NaCl. The seedling lengths (radicle and plumule) and seed vigor index were influenced by significant interaction between the primer and salinity, where EDTA enhanced better seedling growth than the other primers when the salinity did not exceed 150 mM. OMR-LSR-SY maize line did not show tolerability at this concentration. Similarly, EDTA and SA treated maize lines showed lower accumulation of reactive oxygen species such as superoxide anion radical (O2-), hydrogen peroxide (H2O2), as well as a decrease in the malondialdehyde (MDA) contents, most importantly in SWAN-LSR-Y and BR9928-OMR-SR-Y maize lines. Catalase (CAT) and superoxide dismutase (SOD) activities were enhanced in SWAN-LSR- Y and BR9928-OMR-SR-Y upon application of EDTA.